2023
DOI: 10.1186/s12939-022-01759-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing inequities in maternal and child health in rural Guatemala through the CBIO+ Approach of Curamericas: 7. The empowering effect of Care Groups

Abstract: Background While there is extensive published evidence regarding the effectiveness of the Care Group Approach in promoting community-wide health behavior change, there is no published evidence regarding its empowering effect on its participants. Our study aimed to understand if the Care Group Approach as applied in the Curamericas/Guatemala Maternal and Child Health Project in isolated rural mountainous communities in Guatemala produced evidence of empowerment among the female participants. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The context of severe gender inequity among Indigenous populations living in rural Guatemala underlines the need for developing new approaches that promote women's empowerment and address some of the underlying societal norms that have reinforced the traditional dominance of males [25]. Experiences with previous Curamericas Global projects in Guatemala and Liberia using the Care Group Approach, together with experiences from many other Care Group projects implemented by other organizations in other settings [26][27][28][29], have suggested that Care Group participation is an empowering process, but no formal assessment of this hypothesis has been reported prior to the publication of Paper 7 in this series [30]. Paper 7 is a qualitative study that focuses exclusively on how Care Groups-one component of the Expanded Census-Based, Impact-Oriented (CBIO+) Approach described in this paper-led to the empowerment of the Project staff who supported Care Groups, the Care Group Volunteers, and the women who were taught by the Care Group Volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…The context of severe gender inequity among Indigenous populations living in rural Guatemala underlines the need for developing new approaches that promote women's empowerment and address some of the underlying societal norms that have reinforced the traditional dominance of males [25]. Experiences with previous Curamericas Global projects in Guatemala and Liberia using the Care Group Approach, together with experiences from many other Care Group projects implemented by other organizations in other settings [26][27][28][29], have suggested that Care Group participation is an empowering process, but no formal assessment of this hypothesis has been reported prior to the publication of Paper 7 in this series [30]. Paper 7 is a qualitative study that focuses exclusively on how Care Groups-one component of the Expanded Census-Based, Impact-Oriented (CBIO+) Approach described in this paper-led to the empowerment of the Project staff who supported Care Groups, the Care Group Volunteers, and the women who were taught by the Care Group Volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…The other papers in this supplement describe the implementation research methods [38] as well as the effects of the Project on population coverage of key maternal and child health interventions [39], nutrition [40], mortality [41], quality of maternity care at Community Birthing Centers [42], and women's empowerment [36] and well-being [43,44]. The final two papers in the supplement concern assessments of staff and key stakeholders about the CBIO+ Approach [45] and a summary of the findings along with a discussion of the broader implications of this work [46].…”
Section: Guatemala Equity and Healthmentioning
confidence: 99%